Monitoring Trends in Light Pollution in Nakhon Ratchasima Province Based on Nighttime Satellite Imagery - Chaiyakarm, Thanyarat; Silayot, Waranya (Burapha Science Journal, 2026)
This article aimed to analyze and monitor expansion of light pollution from nighttime light (NLT) images during 2013 – 2021 in Nakhon Ratchasima province using nighttime satellite imagery from Suomi National Polar-orbiting Partnership (Suomi-NPP), Visible Infrared Imager Radiometer Suite (VIIRS) based on supervised classification and compared to unsupervised classification. Classification and monitoring results of both methods are consistent. Light pollution could be classified into 5 levels, namely, the highest intensity of light pollution ranged from 18.17 - 86.01, the high intensity ranged from 8.38 - 18.16, the medium intensity ranged from 3.14 - 8.37, the low intensity ranged from 0.91 – 3.40, and the lowest intensity ranged from 0.01 – 0.90. It was found that urban areas were more likely to have light pollution at the highest, high, medium, low and the lowest intensity. Light pollution has intensified every year in the areas of 39.93, 116.63, 353.05, 1,741.79, and 81.55 square kilometers, respectively. The light pollution expansion followed transportation routes, especially Mittraphap Road, the main road considered as the gateway to the northeast region that passes through Nakhon Ratchasima, and was concentrated in the inner city of the province. The analysis of the relationship between nighttime light pollution and population density was conducted using simple linear regression analysis and Pearson’s correlation coefficient. The statistical significance level was set at 0.05. According to the study, the coefficient of determination (R2) light pollution and population density was 0.4956, showing a moderate level of relationship.